Analysis of echocardiographic video by dynamic mode decomposition. Issue 1 (21st November 2020) - Mizuno, Shuya; Oneyama, Fuyuki; Sugino, Masato; Semba, Hiroaki; Jimbo, Yasuhiko; Kotani, Kiyoshi
Abstract: Ultrasonography is a popular method used for medical diagnosis since it is non‐invasive and does not require extensive equipment. However, it requires appropriate control of the probe position and orientation, which is difficult even for experts. As an approach to realize automatic ultrasonography, we analyze echocardiography video using dynamic mode decomposition (DMD) to obtain its feature value. The feature value can be calculated from the dominant modes extracted using DMD. This gives the dynamics on the structure which exhibits pulsating modes, and the entire heart structure can be extracted as well from the stationary mode.